Study the Virtue of Patience: Lessons from Surah Al-Baqarah and Ali Imran in the Qur'an - M. Mustholiq Alwi; Sayyid Husein; Witsarut Lohwithee (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: The aim of this research is to determine the concept of patience education and the implementation of patience education in Q.S surah al-Baqarah verses 45, 153, 294. Methodology: The research used by researchers is library research, this research involves collecting data related to the research object. Data analysis in the form of non-statistical analysis is suitable for descriptive data or textual data. Main Findings: The findings in this research provide a little more knowledge about: The important education of patience which has been explained in Q.S surah al-Baqarah verses 45, 153, 294 and Ali Imran verses 125, 186, 200, apart from providing calm for life. Patience also has the function of solving problems well and not being hasty in carrying them out, so that people who implement this trait will find it easy to obey Allah and His Messenger. Novelty/Originality of this study: This research carries originality in exploring the dimensions of patience education contained in the verses of the Qur'an, especially Surah Al-Baqarah verses 45, 153, and 249, as well as Ali Imran verses 125, 186, and 200. The focus of the research is on analysis in-depth understanding of the historical, linguistic context and interpretation of these verses, in order to reveal the nuances and wisdom contained in patience education. Thus, this research makes an important contribution in enriching the experience of Islamic religious education in madrasah and increasing its relevance to the demands of the times.